Food handling behaviors of consumers when grilling poultry - Terry, Taylor Lauren (Kansas State University, 2017)
Research has shown that many consumers do not use the proper food safety practices when cooking in the home. Although many studies have been conducted to observe the food safety behaviors and practices in a domestic home kitchen, the food safety behaviors of consumers when using an outside grill has not been vastly explored. The objective of this study was to gain insight on consumers' food safety practices and behaviors when preparing meat and poultry on an outdoor grill. A nationwide survey of grilling consumers (n=1024) was conducted to evaluate the food handling behaviors of consumers who use an outdoor grill to prepare meat and poultry. The survey consisted of 50 questions based on the four core practices of food safety: clean, separate, cook, and chill. The results showed that there was low adherence to consumers not rinsing meat or poultry before preparation, separating utensils for raw and cooked meat, and using a thermometer to ensure doneness. Respondents who grilled poultry followed safer food handling practices than respondents who grilled meat. An observational study (n=30) was conducted to observe consumers prepare poultry products on an outdoor grill. Participants were assessed on handwashing skills, cross contamination behavior, and how they determined the doneness of the poultry. This study illustrated that consumers were not washing their hands thoroughly, especially after handling packaging. Many consumers were observed contaminating surfaces or items in their kitchen after touching the raw poultry. Consumers also failed to use clean utensils for the cooked poultry after using the utensil on raw poultry. Consumers used several methods to determine the doneness of the poultry. Visual cues such as looking at the appearance or color of the poultry was primarily used by consumers to check if the poultry was fully cooked, followed by piercing or cutting the poultry open and using a thermometer. Thermometer use in this study was found to be higher than the usage in prior studies. A separate study assessed poultry grilling recipes (n= 242) for a specified temperature of doneness and additional food safety information. Recipes from cookbooks, magazines, and online sources were evaluated. Over half of the recipes did not specify a temperature of doneness, but used time, visual or textural indications to determine doneness. The findings of this research show that consumers could benefit from education to improve their food handling skills when preparing meat or poultry on an outdoor grill. Educational efforts should focus on proper handwashing procedures, how to reduce cross contamination and the importance of using a thermometer to ensure doneness.
Keywords: Poultry; Grilling; Safe; ConsumersFood